2016
DOI: 10.1089/neu.2014.3724
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinase-2, Matrix Metalloproteinase-9, and Vascular Endothelial Growth Factor in the Development of Chronic Subdural Hematoma

Abstract: Chronic subdural hematoma (CSDH) is an inflammatory and angiogenic disease. Vascular endothelial growth factor (VEGF) has an important effect on the pathological progression of CSDH. The matrix metalloproteinases (MMPs) and VEGF also play a significant role in pathological angiogenesis. Our research was to investigate the level of MMPs and VEGF in serum and hematoma fluid. Magnetic Resonance Imaging (MRI) shows the characteristics of different stages of CSDH. We also analyzed the relationship between the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
1
40
1
3
Order By: Relevance
“…Therefore, an excess of VEGF is capable of inducing angiogenesis and excessive vascular permeability, which may contribute to the ongoing rebleeding implicated in CSDH growth [22]. This is supported by correlations between VEGF concentrations and the CSDH imaging subtypes which are thought to reflect increased rebleeding [23, 48]. Further to this, higher levels of VEGF expression in the outer membrane have been associated with a higher probability of CSDH recurrence [53].…”
Section: Angiogenesismentioning
confidence: 99%
“…Therefore, an excess of VEGF is capable of inducing angiogenesis and excessive vascular permeability, which may contribute to the ongoing rebleeding implicated in CSDH growth [22]. This is supported by correlations between VEGF concentrations and the CSDH imaging subtypes which are thought to reflect increased rebleeding [23, 48]. Further to this, higher levels of VEGF expression in the outer membrane have been associated with a higher probability of CSDH recurrence [53].…”
Section: Angiogenesismentioning
confidence: 99%
“…On the other hand, CSDH was recently suggested to be formed through complex processes including angiogenesis, fibrinolysis and inflammation [ 14 ], and the recurrence of CSDH follows the same process as formation. There is strong evidence to show that vascular endothelial growth factor (VEGF) was related to the generation and steady increase of CSDH fluid volume [ 15 17 ] as well as the risk of CSDH recurrence [ 18 ]. Interestingly, Lin et al observed that VEGF expression was positively correlated with BUN [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CSDH was recently suggested to be formatted through complex processes including angiogenesis, fibrinolysis and inflammation [14], and the recurrence of CSDH follows the same process as formation. Strong evidence has been provided that vascular endothelial growth factor (VEGF) was related to the generation and steady increase of CSDH fluid volume [15][16][17] as well as the risk of CSDH recurrence [18]. Interestingly, Lin et al observed VEGF expression was positively correlated with BUN [19].…”
Section: Discussionmentioning
confidence: 99%